Italian expert‐based recommendations on the use of photo(chemo)therapy in the management of mycosis fungoides: Results of an e‐Delphi consensus. Issue 4 (1st February 2021) - Grandi, Vieri; Baldo, Antonello; Berti, Emilio; Quaglino, Pietro; Rupoli, Serena; Alaibac, Mauro; Alberti‐Violetti, Silvia; Amerio, Paolo; Brazzelli, Valeria; Bruni, Pier Luigi; Calzavara‐Pinton, Piergiacomo; Parodi, Aurora; et al.
Abstract: Background: Phototherapy is a mainstay for the treatment of MF. However, there is scarce evidence for its use, mostly due to the lack of a unified schedule. Aims: The primary aim of this study was to establish the first structured, expert‐based consensus regarding the indications and technical schedules of NB‐UVB and PUVA for MF. The secondary aim was to determine the consensus level for each specific item. Materials & Methods: E‐delphi study. Item‐specific expert consensus was defined as the number of "Totally Agree" results to ≥80% of the panelists. Cronbach alpha index ≥0.7 was used as a measure of homogeneity in the responses among questions related to the same topic. Results: Overall, there was a high homogeneity among responders (0.78). On specific topics, the highest grade was observed for technical items (0.8) followed by indications for early (0.73) and advanced stages (0.7). Conclusions: Items related to the most canonical indications of phototherapy and to treatment schedules showed the highest agreements rates. There is consensus about the use of standardized treatment schedules for the induction and consolidation phases for NB‐UVB and PUVA in MF.